Layer 6 Corticothalamic Neurons Activate a Cortical Output Layer, Layer 5a - Kim, Juhyun (Society for Neuroscience, 2014)
Layer 6 corticothalamic neurons are thought to modulate incoming sensory information via their intracortical axons targeting the major thalamorecipient layer of the neocortex, layer 4, and via their long-range feedback projections to primary sensory thalamic nuclei. However, anatomical reconstructions of individual layer 6 corticothalamic (L6 CT) neurons include examples with axonal processes ramifying within layer 5, and the relative input of the overall population of L6 CT neurons to layers 4 and 5 is not well understood. We compared the synaptic impact of L6 CT cells on neurons in layers 4 and 5. We found that the axons of L6 CT neurons densely ramified within layer 5a in both visual and somatosensory cortices of the mouse. Optogenetic activation of corticothalamic neurons generated large EPSPs in pyramidal neurons in layer 5a. In contrast, excitatory neurons in layer 4 exhibited weak excitation or disynaptic inhibition. Fast-spiking parvalbumin-positive cells in both layer 5a and layer 4 were also strongly activated by L6 CT neurons. The overall effect of L6 CT activation was to suppress layer 4 while eliciting action potentials in layer 5a pyramidal neurons. Together, our data indicate that L6 CT neurons strongly activate an output layer of the cortex.